Nakshi Kantha: Embroidered Quilts and Narratives of Social Transformations in Nineteenth-Century Bengal - Chakravarty, Suchandra (Romanticism on the Net)

(untitled) (Université de Montréal, 2021)
This essay seeks to re-evaluate nakshi kantha, a women’s quilting tradition in Bengal, and reconfigure the discourse around it. The quilts came in various sizes and shapes, depending on what utility they served. The focus of this essay will be on specimens of the large rectangular pieces, meant to be coverlets or rugs to sit upon, that were called sujni kantha. The art of covering the quilted surface with elaborate patterns flourished in colonial Bengal in the nineteenth century. The sweeping changes in the sociopolitical fabric of the region that began with the ascendance of British power after the Battle of Plassey accelerated in the second part of the nineteenth century. The embroidered tableaux stitched into the surface of the sujni kantha bear witness to some of these rapid changes. The pieces, which were made in rural Bengal, have been collected in museums across the world, as well as in India. They emerged as collectors’ objects around the 1930s, buoyed by a nationalist discourse that sought to foreground the spiritual autonomy of India in its long-standing traditions of art and craft. A product of women’s labour inscribed with women’s unique perspectives on change has thus been de-historicized and seen as idealized examples of women’s service, patience, and cultural purity – values espoused by the nationalist elite of India. This article seeks to locate nakshi kantha within the specific historical circumstances of their production and circulation and to see them as registers of a specifically feminine perspective on social change. Partha Chatterjee's well-accepted thesis that binaries of inside/outside that developed in the latter half of colonial rule played out along gendered lines, enjoining a restrictive, homebound life upon women, requires qualification. The sujni kantha specimens I examine challenge colonial stereotypes of native women relegated to the shadowy inner quarters of zenanas stuck in time, while also resisting the nationalist construct of idealized Indian womanhood.